2019
DOI: 10.1088/1755-1315/388/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular assessment of several cultivars of bread wheat Triticum aestivum L. under different types of irrigation water

Abstract: The experiment was carried out at the second research station, College of Agriculture, Al-Muthanna University during the winter season 2018-2019, to investigate the performance of four wheat cultivars namely Rasheed, IBA99, Bhooth and Abu Graib subjected K+ supplants to antagonize Na+ effect on growth, yield and genome of four wheat cultivars. Subsequently, varying irrigation water qualities were applied, namely Euphrates river water of 2.4 ds.m-1 electrical conductivity (EC), river water + 400 ppm of K+, sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…With increased salinity levels (from 2 to 16 ds/m), the chlorophyll and protein content also enhanced significantly in the tolerant wheat genotypes i.e., Dijla, 2H, and 3H, while the reduced rate of the said two components was recorded in the control cultivars Ibaa99 and Rabia. These present results were having a great analogy with the findings of Al-Burki et al (2019) who studied molecular performance assessment of bread wheat (Triticum aestivum L.) cultivars under several types of irrigation water. Rady et al (2019) findings also indicated that the reduction in the chlorophyll content and protein percentage in the wheat leaves under salt stress conditions can be attributed to a decrease in photosynthesis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With increased salinity levels (from 2 to 16 ds/m), the chlorophyll and protein content also enhanced significantly in the tolerant wheat genotypes i.e., Dijla, 2H, and 3H, while the reduced rate of the said two components was recorded in the control cultivars Ibaa99 and Rabia. These present results were having a great analogy with the findings of Al-Burki et al (2019) who studied molecular performance assessment of bread wheat (Triticum aestivum L.) cultivars under several types of irrigation water. Rady et al (2019) findings also indicated that the reduction in the chlorophyll content and protein percentage in the wheat leaves under salt stress conditions can be attributed to a decrease in photosynthesis.…”
Section: Discussionsupporting
confidence: 84%
“…54 (4) 780-788. http://doi.org/10.54910/sabrao2022.54.4.9 agricultural sector faces several challenges, including abiotic stress, which causes significant losses through a negative impact on the growth and productivity of crops, including wheat (Dwivedi et al, 2018;Gaballah et al, 2021;Farhood et al, 2022). Salinity is the second most important abiotic stress after drought, which significantly affects wheat production, and it showed limited tolerance to the salinity stress (Al-Burki et al, 2019). Salinity stress leads to negative effects on the transport chain of elements and cell enlargement and division in the growth areas of the plants, as well as reducing the growth, dry mass, leaf size, and eventually decrease the grain production (EL-Sabagh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivar Mawada exhibited the highest mean value of 118.15 stomata mm -2 , whereas the cultivar Bohuth22 demonstrated the lowest mean value of 78.70 stomata mm -2 , resulting in a growth rate of 50.13%. This disparity in performance can potentially be attributed to genetic variations among the cultivars, as supported by the findings of [12]. Regarding the interaction between the two cultivars and colchicine alkaloid, it was observed that the treatment (V2 C2) exhibited the highest average of stomata density (132.6 stomata mm -2 ) in comparison to the lowest average recorded in the treatment (V3 C2) which amounted to (63.0 stomata mm -2 ).…”
Section: 111number Of Stomata (Stoma MM -2 )mentioning
confidence: 66%
“…At each primer, the selected genotypes divided into two or three bands with the local cultivars under high salinity condition. These bands showed high variation between the selected genotypes and local cultivars, this variation maybe concern with the differences between them in their salt tolerance, because in the previous studies these selected genotypes considered as high tolerance to salinity, while the local cultivars were sensitive to salinity [4,5].…”
Section: Genetic Distancementioning
confidence: 88%
“…Molecular markers play a critical role in improving the efficiency of classical breeding programs, including selection, detecting genetic variations, in accelerating the transfer and accumulation of desirable traits in the genotypes, thus increasing agricultural production, breeding for stress tolerance has proven difficult, but there are greater chances of selecting and developing superior species when there is a lot of genetic diversity [2]. The discovery of differentially expressed salt tolerance genes in wheat was accomplished using various techniques, closed systems, such as microarrays and RT-PCR, have traditionally been used extensively in plant gene expression research [3,4]. cDNA-AFLP (cDNA-Amplified fragment length polymorphism) has been effectively utilized to measure transcript abundance and produce expression data in wheat with no requirement for prior knowledge of the organism's genome or transcriptome in open systems [5].…”
Section: Introductionmentioning
confidence: 99%